Free Tissue Transfer in Pressure Ulcer Reconstruction: A Systematic Review - Robertson, Chelsi; Patterson, Charles; Hilaire, Hugo St.; Lau, Frank H. (Journal of Reconstructive Microsurgery Open, 2021)
Background Pressure ulcers (PUs) affect 2.5 million people in the United States annually and incur health-care costs of 11 billion dollars annually. Stage III/IV PU often require local flap reconstruction. Unfortunately, PU recurrence is common following reconstruction; recurrence rates as high as 82% have been reported. When local flap options are inadequate, free tissue transfer may be indicated but the indications have yet to be delineated. To develop evidence-based guidelines for the use of free flaps in PU reconstruction, we performed a systematic review.Methods A systematic review of the available English-language, peer-reviewed literature was conducted using PubMed/MEDLINE, Google Scholar, Scopus, EMBASE, and the Cochrane Database of Systematic Reviews. Articles were manually reviewed for relevance.Results Out of 272 articles identified, 10 articles were included in the final analysis. Overall, this systematic review suggests that free-flap PU reconstruction yields fewer recurrences compared with local flaps (0–20 vs. 13–82%). Further, several types of free flaps for PU reconstruction were identified in this review, along with their indications.Conclusion Free tissue transfer should be considered for recurrent PU. We offer specific recommendations for their use in PU reconstruction.
Keywords: pressure ulcers; pressure sores; free flaps; free tissue transfer; recurrence